ANALISIS KESALAHAN SISWA KELAS X IPA 1 SMAN 2 PEKANBARU DALAM MENYELESAIKAN SOAL PERTIDAKSAMAAN RASIONAL DAN IRASIONAL - Gema Raufany; Titi Solfitri (Jurnal Prinsip Pendidikan Matematika, 2019)
This study aimed to determine students' mistakes in solving mathematics problems on the rational and irrational inequality of one variable. This research is a qualitative descriptive study. The research subjects consisted of 36 students consisting of 17 boys and 19 girls. The research instrument used was a learning achievement test consisting of three items that referred to Basic Competence (KD) 3.2 Explain and determine the resolution of rational and irrational inequalities of one variable. From KD 3.2 developed into three Indicators of Competency Achievement (IPK). Each item measures a different IPK. Students' answers were analyzed descriptively qualitatively by looking at the types of mistakes students made on each item. The results showed that the mistakes made by students were concept errors, principle errors, and operating errors. The mistakes made by students are caused by students not being careful in solving problems and not understanding the rules of algebraic operations.